Y-shaped novel AIEE active push-pull quinoxaline derivatives displaying acidochromism and use towards white light emission by controlled protonation. (November 2021) - Gupta, Shalu; Milton, Marilyn Daisy
Abstract: A series of novel Y-shaped push-pull quinoxaline derivatives 2a-2f with quadrupolar and tripodal arrangement having quinoxaline as an electron acceptor (A ) and biphenyl and phenyl as an electron donor (D ), was designed, synthesized and characterized. Single crystal XRD studies depicted the twisted conformation for quadrupolar quinoxaline derivative 2a . All compounds displayed positive solvatochromism upon increasing solvent polarity from toluene to DMSO. Further, the aggregation studies confirmed the presence of aggregation induced emission enhancement (AIEE) characteristics. Quadrupolar derivatives 2a and 2f displayed nearly five-fold emission enhancement while tripodal derivatives 2b-2 e displayed much lesser emission enhancement on aggregation in THF-water mixture. The photophysical studies were also explored in the presence of acid. Visual colour changes from colourless to light yellow or red under day light, and emission change from violet or indigo to green were observed in solution upon addition of TFA. The spectral and visible colour changes were reversed upon addition of TEA. A controlled protonation of tripodal derivative 2c in chloroform solution caused white photoluminescence and thus may have potential application in white light emitting diodes. Graphical abstract: Image 1 Highlights: Design and synthesis of novel push-pull quinoxaline derivative. AIEE behaviour in THF-Water mixed solvent. Reversible volatile acid sensing. Acid induced white light emission for tripodal derivative 2c. Fabrication of filter paper strips for volatile acid sensing.